Gendered-Value Chain Opportunities and Challenges in Seaweed Aquaculture: The Changing Gender and Socio Economic Dynamics in Mwazaro and Kibuyuni Villages, South Coast Kenya - Kimanga, Faith; Ladan, Lutsili; Mirera, David; Maundu , Anne; Moyoni, Hellen; Bironga, Chadwick; Onyango, Joel (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Globally, seaweed aquaculture is one of the key economic activity in coastal regions. It has emerged as a livelihood source in Kibuyuni and Mwazaro villages in south coast Kenya, fostering economic resilience and gender empowerment. This study examined gender-associated opportunities and challenges within the seaweed value chain, emphasizing labor distribution, economic contributions, and barriers to participation. A mixed-methods approach was employed, incorporating both qualitative and quantitative data from 155 respondents. The findings indicate that women dominate the activity engaging at different levels of the value chain, from farming to processing, while men largely control marketing. Seaweed farmers earn an average of USD 56 per 45-day production cycle. Seaweed farming, however, faces challenges such as a lack of technology, poor farming techniques, ineffective resource management, environmental factors, inadequate knowledge and skills, inadequate financial support, and inadequate farm inputs. Despite these challenges, the study established that the economic and social benefits outweigh the challenges. The findings suggest that targeted interventions addressing financial and market disparities can significantly enhance gender equity and sustainability. Additionally, these patterns highlight the gendered nature of labour division in the seaweed value chain. It is concluded that gender-based economic empowerment and sustainable development interventions are necessary to foster inclusive growth, resilience in coastal communities, and strengthen women’s participation in the seaweed value chain. Seaweed aquaculture can contribute to inclusive economic growth in coastal communities especially in Kenya and the Western Indian Ocean at large.
Keywords: Seaweed, Value chain, Gender empowerment, South coast Kenya